RECONSTRUCTIVE SURGERY OF COMBINED INJURIES OF THE UPPER LIMBS - M.KH. MALIKOV; G.D. KARIM-ZADE; A.A. DAVLATOV; E.K. IBRAGIMOV; A.N. KAMOLOV; N.A. MAKHMADKULOVA; KHAYRULLOI NARZILLO; KH.F. MIRZOBEKOV (Avicenna Tajik State Medical University, 2018)
Objective: Improving the results of surgical correction of combined injuries of the upper limbs. Methods: The results of surgical treatment of 58 patients analyzed (37 men and 21 women) with combined bone and vascular lesions of the upper limbs between the ages of 4 and 67 years. The etiological factors of damages were: cutting wounds (30), transcondular fractures (17), anterior forearm dislocation (5), and gunshot wounds (6). Damage of the median nerve by the sharp edges of the bone fragments was observed in 2, traction of the nerve with axonotmesis - in 3 victims. The circular suture of the brachial artery (11) was performed with a diastasis of no more than 3 cm; in case of diastase more than 3 cm, autovenous vascular plasty (13) was performed; when the brachial artery bifurcation was damaged, an autovenous shunting was performed (5). In case of simultaneous damage to the radial and ulnar arteries, in 16 cases the suture (9) and autovenous plasty (7) were performed; with isolated injuries to the radial (8) and ulnar (5) arteries, a circular suture was used. Results: In the immediate postoperative period, thrombosis of the restored arteries observed in 4 patients (6.8%). In the long-term period, when studying the degree of blood circulation of an extremity on the basis of Duplex scan in 46 patients, only in one observation did the ulnar artery thrombosis take place, the remaining vessels were passable. The degree of regeneration of the restored nerve trunks was estimated according to the electroneuromyography data: during axonotmesis, all types of sensitivity recovered within 6 months. A positive discrimination test S1-S2 observed 1.5 years after the epineural suture of the median nerve. Conclusion: Timely diagnosis and the provision of adequate specialized care for bone and vascular injuries allows to achieve full rehabilitation of the victims and, along with a reduction in disability, significantly improves the quality of life of patients.